Enhanced Resistance Against Junin Virus Infection Induced by Corynebacterium parvum - Budzko, Delia B. (1978)
The effects of intraperitoneal administration of Corynebacterium parvum on the course of Junin virus infection in mice were investigated. This treatment produced enhanced resistance to the virus infection, evidenced by an increase in both survival times and the proportion of survivors. The protective effect was dependent upon the dose of C. parvum, and 280 μg/g of body weight was found to be the optimal dose. In various experiments, about 80% of the infected animals receiving this dose survived, whereas survival ranged between 0 and 20% among untreated infected mice. Maximal protection was afforded by C. parvum when administered simultaneously with the virus. A smaller but significant degree of resistance was induced by C. parvum given 3 or 6 days after infection. C. parvum injected before infection was ineffective. Viral titers measured in the brains of C. parvum-treated and untreated mice at various times after infection were found to be comparable. In addition, there were no significant differences between circulating-antibody titers measured either by neutralization tests or by complement fixation. Depression of the reticuloendothelial system by treatment with silica particles also resulted in enhanced resistance to Junin virus infection, suggesting that the protective effect of C. parvum is not likely to be due merely to its capacity to stimulate macrophages. The present data, highlighting that the presence of high titers of Junin virus and disease do not necessarily correlated, suggest that in mice this disease is not the consequence of cell damage caused directly by the virus but of a still undefined indirect mechanism induced by the virus, not necessarily mediated by macrophages.